Skin Microbiota and Clinical Associations in Netherton Syndrome - Veera Sillanpää; Tatiany Aparecida Teixeira Soratto; Elina Eränkö; Mauricio Barrientos-Somarribas; Katariina Hannula-Jouppi; Björn Andersson; Annamari Ranki (Elsevier, 2021)
Netherton syndrome (NS) is a rare, life-threatening syndrome caused by serine protease inhibitor Kazal-type 5 gene (SPINK5) mutations, resulting in skin barrier defect, bacterial skin infections, and allergic sensitization in early childhood. Recent data on adult patients with NS suggest that the presence of Staphylococcus aureus further promotes barrier disruption and skin inflammation. We analyzed the skin microbiota by shotgun sequencing in 12 patients with NS from eight Finnish families with healthy family controls as the reference and correlated the findings with allergen-specific IgE prevalence, immune cell phenotype, and infection history of the patients. Compared with healthy family controls, skin microbiome diversity and normal skin site variability were measurably decreased in patients with NS. No correlation was found between allergic sensitization and skin microbiota as such, but low circulating CD57+ and/or CD8+ T cells significantly correlated with lower microbial diversity and less abundance of S. aureus (P < 0.05). S. aureus was the most prevalent species in patients with NS but also Streptococcus agalactiae was abundant in four patients. The genomic DNA relative abundance of S. aureus secreted virulence peptides and proteases PSMα, staphopain A, and staphopain B were increased in most of the samples of patients with NS, and their abundance was significantly (P < 0.05) associated with recurrent childhood skin infections, confirming the clinical relevance of S. aureus dominance in the NS skin microbiome.